Organização e planejamento agrícola familiar na comunidade são Raimundo Nonato, Acará-PA - SANTOS, Deyse do Socorro da Silva (2021)
The present work presents the result of the research about the agricultural organizations family production directed to the operation of the properties and its importance in the productive systems practiced by the farmers of the São Raimundo Nonato community in the city of Acará, Pará. It is a methodology based on qualitative research, using questionnaires, semi-structured interviews and gathering information through dialogues. It was observed in the collected data that the farms present a similar characteristic in the context of the dynamics used to develop their cultivation activities, being that the developed activities and the productions of the referred one aim for the sustainability of the families, and secondly a generation of income to contribute to complement family support and community development. The results of this research show the way of life of the community dwellers, especially of agricultural activities, which are directed to both subsistence and income supplementation. As well as the new techniques used by farmers to manage their farms. In addition, it is important to remember the potential of organizations and dynamics adopted by farmers for community development.